Answer:
D. 85.7%
Step-by-step explanation:
its figuring out the percentage decrease
so you would go
35-5= 30
30/35 x 100 = 85.7
1(6x-9)=(4x-6)
One solution was found :
x = 3/2 = 1.500
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
1*(6*x-9)-((4*x-6))=0
Step by step solution :
Step 1 :
Step 2 :
Pulling out like terms :
2.1 Pull out like factors :
6x - 9 = 3 • (2x - 3)
Equation at the end of step 2 :
3 • (2x - 3) - (4x - 6) = 0
Step 3 :
Equation at the end of step 3 :
2x - 3 = 0
Step 4 :
Solving a Single Variable Equation :
4.1 Solve : 2x-3 = 0
Add 3 to both sides of the equation :
2x = 3
Divide both sides of the equation by 2:
x = 3/2 = 1.500
One solution was found :
x = 3/2 = 1.500
Answer:
GCF=4
Step-by-step explanation:
16/4=4
24/4=6
36/4=9
Answer:
C
Step-by-step explanation:
To find the appropriate equation, notice the red graph has shifted up about 6 units. This means that
which is shifted by -3 will move 6 up. -3+6= 3. This means the function will have +3. Only B and C are options. Now test a point. Notice the red function crosses the y-axis at about 5 or 6 when x=0.
![g(x) = 2^x+3\\g(0) = 2^0+3\\g(0)=1+3\\g(0)=4](https://tex.z-dn.net/?f=g%28x%29%20%3D%202%5Ex%2B3%5C%5Cg%280%29%20%3D%202%5E0%2B3%5C%5Cg%280%29%3D1%2B3%5C%5Cg%280%29%3D4)
This function doesn't match.
![f(0) = 3*2^0+3\\f(0) = 3*1+3\\f(0)=6](https://tex.z-dn.net/?f=f%280%29%20%3D%203%2A2%5E0%2B3%5C%5Cf%280%29%20%3D%203%2A1%2B3%5C%5Cf%280%29%3D6)
This function matches. Option C is correct.
Answer:
x = t(a+p)/4
Step-by-step explanation
Given the expression
a=4x/t - p
We are to make x the subject of the formula
a=4x/t - p
Add p to both sides
a+p = 4x/t - p+p
a+p = 4x/t
Cross multiply
t(a+p) = 4x
Rearrange
4x = t(a+p)
Divide both sides by 4
4x/4 = t(a+p)/4
x = t(a+p)/4